Design research on developing primary students’ conceptual understanding of area through visual-spatial activities - Utami, Ogi Meita (Universitas Maritim Raja Ali Haji, 2025)
This study examines how primary students develop a conceptual understanding of composite shapes, a topic that many learners find challenging beyond the routine use of formulas. The research was motivated by the persistent issue that instruction in the area in elementary classrooms is often procedural and does not sufficiently foster reasoning about spatial structure, decomposition, and measurement. This study employed a Design Research approach in a sixth-grade classroom (n = 6 students) to iteratively develop and test a Hypothetical Learning Trajectory (HLT) for the learning area of composite shapes through visual-spatial and puzzle-based activities. Data were collected through a pre-test, two instructional activities (Activity 1 and Activity 2), classroom observations, and a post-test. Data were analyzed qualitatively through retrospective analysis aligned, with HLT, supported by descriptive coding of students’ strategies, triangulation of written work, and teacher field notes. Findings indicate that students shifted from purely visual recognition toward more analytical strategies, such as partitioning, conservation, transitivity, and additivity, which emerged during instruction. The results suggest that structured visual-spatial tasks grounded in a realistic context effectively bridge abstract area concepts and classroom practice, informing future instructional design in elementary geometry.